2006
DOI: 10.1128/aac.00437-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity and Mitochondrial Toxicity of Tenofovir Alone and in Combination with Other Antiretrovirals in Human Renal Proximal Tubule Cells

Abstract: We assessed the in vitro toxicity of tenofovir (TFV) and compared it with those of zidovudine (AZT), didanosine (ddI), ritonavir (RTV), and lopinavir (LPV) alone and in combination in human renal proximal tubule epithelial cells (RPTECs). The cells were treated with various concentrations and combinations of the tested antiretrovirals for up to 22 days, and cytotoxicity was determined. In addition, we assessed the levels of mitochondrial DNA (mtDNA) and cytochrome oxidase II (COII) mRNA in RPTECs treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 68 publications
7
41
0
Order By: Relevance
“…TFV is also transported by OAT1, but in in vivo studies, no reduction in mtDNA was observed in the kidney (24). Furthermore, the data reported herein confirm previous observations that TFV does not reduce mtDNA in human RPT cells cultured for up to 3 weeks (18,25,26). Our study indicates that at a high, equimolar concentration (200 M), TDF is significantly less cytotoxic in vitro than ADV.…”
Section: Discussionsupporting
confidence: 81%
“…TFV is also transported by OAT1, but in in vivo studies, no reduction in mtDNA was observed in the kidney (24). Furthermore, the data reported herein confirm previous observations that TFV does not reduce mtDNA in human RPT cells cultured for up to 3 weeks (18,25,26). Our study indicates that at a high, equimolar concentration (200 M), TDF is significantly less cytotoxic in vitro than ADV.…”
Section: Discussionsupporting
confidence: 81%
“…Emtricitabine, elvitegravir, and COBI were also tested for cytotoxicity toward RPTECs, with resulting CC 50 values of Ͼ100, 13.7, and 26.2 M, respectively. These values were consistent with the generally low cytotoxicity of TFV in RPTECs reported previously (11,(23)(24)(25). Coincubation of TFV with either COBI alone or COBI, elvitegravir, and emtricitabine in combination at pharmacologically relevant concentrations showed no measureable cytotoxicity within the range of tested concentrations of TFV (Table 2).…”
Section: Resultssupporting
confidence: 78%
“…TFV by itself exhibited minimal cytotoxicity in RPTECs, even at high concentrations, an observation consistent with prior studies (24,25). Neither COBI alone nor the combination of COBI, elvitegravir, and emtricitabine affected the cytotoxicity of TFV in human RPTECs.…”
Section: Discussionsupporting
confidence: 76%
“…For example, mOat3 was implicated as the major contributor to ddC and ddI transport, and consequently, ddC is shown to be a novel mOat3 substrate. Both ddC and ddI have been shown to be cytotoxic (27)(28)(29)(30). Although Oat1 and Oat3 have significant overlap in the proximal tubule segments (S1-S3), rOat3 has also been shown to be expressed in the thick ascending loop, distal tubule, connecting tubule, and the collecting duct of the outer medulla (31,32).…”
Section: Discussionmentioning
confidence: 99%